MEKANISME PEMBIAYAAN MUDHARABAH UNTUK USAHA KECILDAN MENENGAH (UKM) (Studi Kasus di Koperasi Jasa Keuangan Syariah (KJKS) Mitra Amanah Sejahtera Semarang Tahun 2011-2012) - Achmad Fajaruddin; Aulia Ulfa Nurfitriyani (Islamic Economics Journal, 2014)
Empowerment of SMEs is a strategic step to improve and strength the basis of economic life for most of Indonesian people. During its development, SMEs are still having problems, especially in a capital. To overcome this finance obstacle, it is necessary to improve and develop some access-financing sources. One of them is to activate a cooperative enterprise. ICE of Mitra Amanah Sejahtera is an Islamic financial institution that given a financing provision based on mudharabah system. In this research, the researcher discusses about the mechanism of mudharabah financing conducted by ICE of Mitra Amanah Sejahtera for SMEs. In addition, the researcher continues her research on respondent perceptions toward mudharabah financing. Furthermore, this research was continuing by compare their prior revenue and after engaging into mudharabah financing. This research includes a case study, which used a phenomenological approach. The population in this research was all of SMEs that obtained the mudharabah financing at ICE of Mitra Amanah Sejahtera, amounting to 1500 customers and by slovin formula there are 94 data as a sample. The research comes with a result that the mechanism of mudharabah financing from ICE of Mitra Amanah Sejahtera used the principle to provide a maximum funding on Rp. 1 million, with no collateral and based on trusty principles. In general, mudharabah system that has been undertaken by this cooperative can provide some benefits for its members. Their perceptions toward mudharabah financing at ICE of Mitra Amanah Sejahtera were as follow: these are some benefits that perceived the borrowers (82.98%), there is a significant influence on business development (83.30%), respondent satisfied toward mudharabah mechanism (79.79%), an easy administration (77.66%) and respondent satisfied toward mudharabah contract (81.92%). From paired test result, there is significant difference between the prior revenue and after engaging into financing. Thus, can be seen from small and medium enterprises’ prior revenues and after engaging into mudharabah financing with average revenue of Rp. 261.968. Based on this research, the researcher prefers to suggest the ICE of Mitra Amanah Sejahtera to maintain the mechanism of mudharabah financing, especially in order to develop a micro-economic life from it capital difficulties.